The American Space Commerce Free Enterprise Act of 2017: The Latest Step in Regulating the Space Resources Utilization Industry or Something More?. (February 2019) - Hao, Liu; Tronchetti, Fabio
Abstract: On June 6, 2017, a draft bill entitled the American Space Commerce Free Enterprise Act was introduced to the US House of Representatives. Even though the bill has not been enacted into law yet, its relevance should not be underestimated. Indeed, it not only represents the latest step in regulating the nascent space mining industry but also contains several provisions that, to a large extent, challenges the traditional understanding of basic international space law rules. For example, the draft bill refers to the right of the US entities to engage in space undertaking without conditions or limitations, argues that not all the obligations of the Outer Space Treaty are imputable to those entities, and claims that outer space is not a global commons. In the light of the above, the purpose of the present viewpoint was to review the most innovative, yet controversial, elements of the draft bill and to assess their possible impact on future space resources utilization activities as well as on the overall stability of the space law regime.